Tween as a Substitute for Diethyl Ether in the Formalin-Ether Sedimentation Technique - NA Ahmadi; K Pakdad (Tehran University of Medical Sciences, 2007)
Background: Tween as a substitute for diethyl ether in the formalin-ether sedimentation technique was evaluated for parasite detection.Methods: Fresh fecal material free of parasites with 10% formalin to prepare standardized specimen was thoroughly pooled. This specimen was divided into 5 equal portions; one was without infection, and each of the others was individually seeded with Entamoeba coli, and Giardia lamblia cysts, ova of Ascaris lumbericoides, and Hymenolepis nana. Six hundred and eighty four slides including 228 stool samples for each of formalin-tween, formalin-ether and direct wet mount procedures were examined.Results: The sensitivity of above mentioned procedures were computed 72.1%, 55% and 30 %; their negative predictive value were 69.3%, 58.3% and 47.3%; and their false negative error rate were 27.9%, 45% and 70%, respectively. There were no false-positive results among the 264 specimens previously identified as negative for the presence of intestinal parasites. Therefore, specificity for each technique was 100%.Conclusion: In the range of our study, formalin-tween method proved to be equivalent to or better than formalin-ether technique in concentrating parasite eggs, and cysts, as well as in maintaining characteristic morphology. Tween is more stable, safer, cheaper, and less flammable than that of ether; and promises to be a useful alternative to ether.